2022
DOI: 10.1111/papr.13134
|View full text |Cite
|
Sign up to set email alerts
|

A brief psychological intervention for chronic pain in primary care: Examining long‐term effects from a pilot randomized clinical trial

Abstract: Background: Despite the existence of evidence-based psychological interventions for pain management, there are barriers that interfere with treatment engagement.A brief intervention integrated into primary care reduced barriers and showed promising benefits from pre-to post-intervention. However, it is unknown whether a brief intervention can provide long-term effects. The purpose of this study was to examine whether a brief psychological intervention offered benefits in pain severity, pain interference, pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Moreover, tailoring a behavioral intervention to a target population’s biopsychosocial context can improve treatment outcomes (Eldredge et al, 2016). Though this initial intervention appeared to offer benefits for pain functioning and distress in a pilot trial (Miller-Matero et al, 2021, 2022), future research can evaluate whether a revised intervention is efficacious in a fully powered trial.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, tailoring a behavioral intervention to a target population’s biopsychosocial context can improve treatment outcomes (Eldredge et al, 2016). Though this initial intervention appeared to offer benefits for pain functioning and distress in a pilot trial (Miller-Matero et al, 2021, 2022), future research can evaluate whether a revised intervention is efficacious in a fully powered trial.…”
Section: Discussionmentioning
confidence: 98%
“…This brief intervention may encourage engagement and adherence in treatment while still offering the benefits of lengthier interventions. Indeed, this brief psychological intervention for persistent pain management appears to lead to improvements in pain severity, pain catastrophizing, and depression compared to a treatment-as-usual control group (Miller-Matero et al, 2021), and may have longer term benefits similar to that of lengthier interventions (Miller-Matero et al, 2022). Understanding the components that were perceived to be the most helpful would be useful to ensure high impact in this brief intervention.…”
mentioning
confidence: 99%
“…This secondary analysis was a part of a randomized controlled trial of a five-session psychological intervention for chronic musculoskeletal pain in primary care and was approved by the Institutional Review Board at Henry Ford Health (Miller-Matero et al, 2021, 2022). This study is registered at Clinicaltrials.gov.…”
Section: Methodsmentioning
confidence: 99%
“…In the final session, the clinician reviewed strategies taught in the initial sessions and helped the individuals identify ways to use strategies in their daily lives. A description of the development of the manual for this intervention and the session components are published, which showed benefits for improving pain and psychological outcomes similar to lengthier manualized psychological interventions for chronic pain (Miller-Matero et al, 2021, 2022). Sessions were initially delivered in-person in a primary care clinic; however, half way through enrollment, we allowed participants to choose in-person visits or video visits.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to treatment as usual, individuals receiving the intervention experienced decreased pain severity, pain interference, pain catastrophizing, and depression from baseline to postintervention. Examination of the longer term follow-up effects in the intervention group (Miller-Matero et al, 2022) showed no differences between intervention and control groups at the 1-month follow-up, but initial improvements in pain severity and pain catastrophizing were maintained at 6 months postintervention. That said, there were no differences between intervention and control groups in pain interference or depression at either 1- or 6-month follow-up.…”
mentioning
confidence: 98%